Structural optimization of a wheel force transducer component for more realistic acquisition of vehicle load data and fracture mechanical evaluation - Jan-Peter Brüggemann (Elsevier, 2021)
Special measuring wheels are used to record vehicle load data. It is important that the data is recorded unaltered and as true to the original as possible. Due to the sensor technology, the measuring wheels are usually heavier than standard rims, which results in an influence on the recorded measurement data.In this paper an approach is shown to develop a structure with the same performance but reduced mass by using CAD and numerical analysis. Due to the geometrically complex structure, the selective laser melting process is chosen as the manufacturing method for the optimized part. The lightweight construction potential can be fully exploited by homogeneously stressing the optimized part and by using the Ti6–4 alloy, which has a higher Young's modulus than the aluminum alloy used so far. The interaction of the methods of technical mechanics, CAD, FEM, and additive manufacturing results in a safety-relevant component that has a mass reduced by almost 40% compared to the previously used component while maintaining the same stiffness. A final crack growth simulation confirms the operationally safe design. Finally, the component was first tested experimentally on a test rig and then installed in a vehicle. All tests were passed successfully.